1999
DOI: 10.1128/aem.65.11.4981-4986.1999
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus salivarius CTC2197 Prevents Salmonella enteritidis Colonization in Chickens

Abstract: A rifampin-resistant Lactobacillus salivarius strain, CTC2197, was assessed as a probiotic in poultry, by studying its ability to prevent Salmonella enteritidis C-114 colonization in chickens. When the probiotic strain was dosed by oral gavage together with S. enteritidis C-114 directly into the proventriculus in 1-day-old Leghorn chickens, the pathogen was completely removed from the birds after 21 days. The same results were obtained when the probiotic strain was also administered through the feed and the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(116 citation statements)
references
References 34 publications
3
105
0
8
Order By: Relevance
“…The spent culture supernatant of the human L. acidophilus strain LB given daily followed infection is active against S. enterica serovar Typhimurium C5 infecting conventional C3H/He/oujco mice, reducing the levels of viable Salmonella in the faeces [172]. Furthermore, L. salivarius CTC2197 colonizing the gastrointestinal tract of Leghorn chickens, is able to prevent S. enteritidis colonization [173]. In contrast, it has been observed that Salmonella survives and persists at a higher level in the faeces of conventional mice treated with L. casei rhamnosus GG given daily [107].…”
Section: Activity Against Salmonellamentioning
confidence: 99%
“…The spent culture supernatant of the human L. acidophilus strain LB given daily followed infection is active against S. enterica serovar Typhimurium C5 infecting conventional C3H/He/oujco mice, reducing the levels of viable Salmonella in the faeces [172]. Furthermore, L. salivarius CTC2197 colonizing the gastrointestinal tract of Leghorn chickens, is able to prevent S. enteritidis colonization [173]. In contrast, it has been observed that Salmonella survives and persists at a higher level in the faeces of conventional mice treated with L. casei rhamnosus GG given daily [107].…”
Section: Activity Against Salmonellamentioning
confidence: 99%
“…The use of L. salivarius as a probiotic in poultry dates from over 15 years and several studies have reported the reduction in colonization by Salmonella Enteriditis (SE) attributed to the competitive exclusion effects of L. salivarius. Pascual et al (1999) dosed strain CTC2197 by oral gavage together with SE directly into the proventriculus in 1-day-old chickens resulting in complete pathogen elimination after 21 days. The same results were obtained when the probiotic was administered in the feed and drinking water.…”
Section: Poultry and Eggs Production And Healthmentioning
confidence: 99%
“…The same results were obtained when the probiotic was administered in the feed and drinking water. The inclusion of CTC2197 in the first-day chicken feed revealed that a concentration of 10 5 CFU per g was enough to ensure the colonization of the GIT of the birds after 1 week, making it a suitable option to minimize Salmonella colonization in chickens (Pascual et al 1999). Similarly, Zhang et al (2007) found that feeding chickens an overnight culture (10 6 -10 8 CFU per chick) of strains Salm-9, List40-1,8 or List40-41 reduced Salmonella carriage in caecal contents by 2Á10, 2Á52 and 2Á20 log CFU per g respectively.…”
Section: Poultry and Eggs Production And Healthmentioning
confidence: 99%
“…Decrease in relative proportion of potential pathogens was also detected. Studies (Watkins et al 1982;Pascual et al 1999) have indicated that the feed treated with probiotics had a competitive exclusion of pathogenic bacteria in host animals. In line with those findings, the relative abundance of potentially pathogenic bacteria for broilers such as Staphylococcus and Escherichia-Shigella reduced in broilers fed diet supplemented with B. subtilis CGMCC 1.1086 in the present study.…”
Section: T0 T1mentioning
confidence: 99%